The Role of Public Relations in Raising Awareness of the Activities of the Gulf Accreditation Center (The International Journal of Educational Sciences and Arts, 2024)
This research deals with “The Role of Public Relations in Raising Awareness of the Activities of the Gulf Accreditation Center”, and aims to explore how the objectives, activities, and practices of public relations affect the level of awareness of the center’s activities, in addition to identifying the obstacles facing these activities and their impact on the effectiveness of awareness. The data were collected using a questionnaire directed to those dealing with the center and analyzed to test a set of hypotheses related to the relationship between these variables. The results showed a statistically significant direct relationship between the objectives of public relations and the level of awareness of its activities, as it was found that the correlation coefficient between them was 0.43, indicating a moderate direct relationship. The results also showed that there is a direct relationship between the activities and practices of public relations and the level of awareness of its activities, with a correlation coefficient of 0.41. As for the obstacles facing public relations, the results showed an inverse relationship with awareness of the center’s activities, as the correlation coefficient was -0.54, indicating that the obstacles negatively affect the effectiveness of awareness. Through regression analysis, it was found that variables related to the objectives, activities, and obstacles of public relations contribute 52% to improving awareness of the center's activities. The differences between males and females, and between clients who differ in years of experience and job title were also tested, as the results showed statistically significant differences between clients' evaluations based on years of experience and job title, indicating the impact of these factors on the evaluation of obstacles. The research recommended increasing awareness in the center about the importance of public relations through workshops and training courses, and allocating greater resources to familiarize employees with the objectives of public relations and their impact on performance. It also recommended intensifying community activities to improve communication with the public, and improving training programs for public relations employees to enhance their skills and increase the effectiveness of awareness activities.
Keywords: Public Relations; Awareness; Activities; Gulf Accreditation Center